Effect of angiotensin receptor blockers on the development of cancer: A nationwide cohort study in korea - Mi‐Hyang Jung; Ju‐Hee Lee; Chan Joo Lee; Jeong‐Hun Shin; Si Hyuck Kang; Chang Hee Kwon; Dae‐Hee Kim; Woo‐hyeun Kim; Hack Lyoung Kim; Hyue Mee Kim; In Jeong Cho; Iksung Cho; et al. (The Journal of Clinical Hypertension, 2021)
Abstract The potential cancer risk associated with long‐term exposure to angiotensin receptor blockers (ARBs) is still unclear. We assessed the risk of incident cancer among hypertensive patients who were treated with ARBs compared with patients exposed to angiotensin‐converting enzyme inhibitors (ACEIs), which are known to have a neutral effect on cancer development. Using the Korean National Health Insurance Service database, we analyzed the data of patients diagnosed with essential hypertension from January 2005 to December 2012 who were aged ≥40 years, initially free of cancer, and were prescribed either ACEI or ARB (n = 293,962). Cox proportional hazard model adjusted for covariates was used to evaluate the risk of incident cancer. During a mean follow‐up of 10 years, 24,610 incident cancers were observed. ARB use was associated with a decreased risk of overall cancer compared with ACEI use (hazard ratio [HR] 0.76, 95% confidence interval [CI] 0.72‐0.80). Similar results were obtained for lung (HR 0.73, 95% CI 0.64‐0.82), hepatic (HR 0.56, 95% CI 0.48‐0.65), and gastric cancers (HR 0.74, 95% CI 0.66‐0.83). Regardless of the subgroup, greater reduction of cancer risk was seen among patients treated with ARB than that among patients treated with ACEIs. Particularly, the decreased risk of cancer among ARB users was more prominent among males and heavy drinkers (interaction P < .005). Dose‐response analyses demonstrated a gradual decrease in risk with prolonged ARB therapy than that with ACEI use. In conclusion, ARB use was associated with a decreased risk of overall cancer and several site‐specific cancers.